Effects of Homoeopathic Single and Minimum Dose on Non-Radiographic Axial Spondyloarthritis—BASDAI Assessment - Kumar, Deepak; Suchiang, Eiphrangdaka L.; Pal, Gautam (Homœopathic Links, 2020)
Early cases of ankylosing spondylitis do not have the typical presentation of radiographic sacroiliitis but present as non-radiographic axial spondyloarthritis (nr-axSpA) where both are varieties of axSpA. Homoeopathic prescription based on totality of symptoms offers a promising relief to nr-axSpA where peripheral joints are also affected. Here, a 27-year-old male patient presented with bilateral heel pain, pain in low back, pain on base of right toes, pain in neck with stiffness for 1 year had refractive response to conventional medication. Diagnosis was confirmed by Assessment of SpondyloArthritis International Society diagnostic criteria for axSpA. Single medicine and minimum dose of Silicea showed its effectiveness on the symptoms' improvement and Bath Ankylosing Spondylitis Disease Activity Index score whereby score of 8.8 (active disease) before treatment changed to 1.2 (inactive or mild disease) after treatment. Various other parameters were assessed accordingly before and after treatment. This case report encourages further exploring the beneficial effects of homoeopathic treatment in clinical condition like axSpA utilising validated scale.
Keywords: ankylosing spondylitis; homoeopathy; non-radiographic axial spondyloarthritis; single medicine